Face-capture with automatic blendshape generation - Nogueira, João Vitor; Sumar, Bruno; Carvalho, Leonardo (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2022: Anais Estendidos da XXXV Conference on Graphics, Patterns and Images, 2022)
The goal of this paper is the development of a system for the production of performance-driven facial animation that automatically generates a blendshape model from input video frames. This simplifies the production of this kind of model to be used in animation projects. The proposed method is designed to be used without the need for expensive hardware, such that any computer with a webcam can run the system.